Thermally-Induced Spin Crossover and LIESST Effect in the Neutral [FeII(Mebik)2(NCX)2] Complexes: Variable-Temperature Structural, Magnetic, and Optical Studies (X = S, Se; Mebik = bis(1-methylimidazol-2-yl)ketone) - De, Siddhartha; Chamoreau, Lise-Marie; El Said, Hasnaa; Li, Yanling; Flambard, Alexandrine; Boillot, Marie-Laure; Tewary, Subrata; Rajaraman, Gopalan; Lescouëzec, Rodrigue (Frontiers in Chemistry, 2018)
Two new iron(II) neutral complexes of bis(1-methylimidazol-2-yl)ketone (Mebik) with molecular formula [FeII(Mebik)2(NCS)2] (1) and [FeII(Mebik)2(NCSe)2] (2) have been synthesized and characterized by magnetic measurements, single-crystal X-ray diffraction and solid state UV-vis spectroscopy. The temperature dependent magnetic susceptibility measurements of crystalline samples of both compound show the occurrence of a gradual spin transition centred at T1/2 = 260 K and 326 K, respectively. The crystal structures of both compounds were determined at different temperatures, below and above the transition, in order to detect the structural changes associated with the spin transition. The main structural modifications, when passing from the low-spin to the high-spin form, consist of an important lengthening of the Fe-N(Mebik) and Fe-N (C-S/Se) distances (by ca. 0.20 Å and 0.18 Å, respectively) and a noticeable variation of the N-Fe-N angles, leading to a more distorted [Fe-N6] octahedron. The spin-transition phenomenon also affects the optical properties, with significant decrease of the intensity of the Metal-to-Ligand charge transfer band upon increasing the temperature. Finally, both complexes exhibit a light-induced excited spin-state trapping under laser light irradiation at low temperature. DFT calculations were also carried out on these complexes in order to rationalise the theoretically predicted magnetic and optical behaviour with those of the experimental one. The results clearly highlights the dramatic alteration of the magneto-structural behaviour of the tris-chelate [FeII(Mebik)3]2+ spin-crossover complex upon substituting one Mebik with NCS and NCSe ligands.